CAPITAL STRUCTURE OPTIMALIZATION OF INDONESIA STATE OWNED ENTERPRISE (SOE) CONSTRUCTION COMPANY USING COST OF CAPITAL APPROACH - Nusya Perdana, Iqbal
Indonesian government has accelerated infrastructure development in past few years to minimize gap with other countries. This can be represented by portion infrastructure development in APBN recently. In several government infrastructure projects, State Owned Enterprise (SOE) as agent of development got credentials from government to execute it. The contracts has made asset of several SOE Construction Company increasing, so has their revenue. However, their highly growth has made them to fund the projects and contracts by external funding.